The Accuracy of Activity Monitors on Land and in the Water: A Pilot Study. Issue 1 (2019) - Michaels, Natalie N.; Stevens, Sandra; Noven, Marnie Vanden; McConnell, Ryan; Sherrow, Kathryn Drescher; Tweddle, Morgan
Abstract : Background. : Activity monitors are becoming ubiquitous in the United States, used by people of all ages. Recently, models have been created for use both on land and in the water, but the accuracy of these monitors is still in question. Methods. : Twelve students at Belmont University walked on a treadmill for 3‐minute intervals at low, moderate, and high intensity while wearing 6 of the more popular land/water activity monitors. They then repeated this activity in the water using a HydroWorx underwater treadmill. These activities were filmed so that the researchers would know the actual step count for comparison. Results. : The most accurate monitors on land and in the water for step count were determined at each of the 3 speeds using correlation, mean step difference, Cohen's d calculation, and paired t testing for significance. Each device had its advantages, with each selected as the first choice for at least 1 of the 6 conditions. None of the devices studied in this research, however, was most accurate in all settings or at all speeds. Relevance. : This study provided valuable information regarding the effectiveness of various activity monitors on land and in the water. Further research is recommended utilizing more specific monitor placement and a larger number of monitors in multiple situations.